THE ROLE OF THE ECONOMY IN GROWING THE REGIONAL ECONOMY IN THE NGORO SUB-DISTRICT, JOMBANG DISTRICT - Wina Nurhayati; Supriyadi Supriyadi; Diyah jannatin; Linda Ratnasari (Jurnal Ekonomi, 2022)
The purpose of this study was to find out the role of the Creative Economy in Growing the Regional Economy in Ngoro District, Jombang Regency. This type of research is a qualitative field research. Sources of data in this study are primary and secondary. Data collection techniques used are interviews (interviews) and documentation. The data analysis method used is descriptive qualitative method. Checking the validity of the findings using the technique of extending the presence of researchers in the field, in-depth observation, triangulation, peer discussion, and checking members, to check the degree of trust. The results show that 1. There are 12 types of Creative Products in Ngoro District, namely Game Applications and Development, Architectural Creative Industry Sub-sector, Interior Design Creative Industry Sub-sector, Advertising or Advertising, Performing Arts Sub-sector, Photography Creative Industry Sub-sector, Culinary Sub-sector, Crafts Sub-sector , Fashion Sub-sector, Creative Music Industry Sub-sector, Publishing Sub-sector, Television and Radio Sub-sector with a total of 63 industry players and most of them are in the culinary and fashion sub-sector. 2. The role of the creative economy in the economic growth of the Ngoro sub-district can be seen in the income from the Ngoro sub-district which increases every year and the poverty and unemployment rates have decreased